Optimalisasi Hasil Belajar Peserta Didik Dengan Pendekatan Kolaboratif Dalam Mengenal Karya Ilmiah KelAS XI SMA Negeri 3 Palembang - R, Refilita; Lestari, Hikmah (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
The aim of this research is to optimize student learning outcomes by using a collaborative approach in recognizing scientific work in class XI SMA Negeri 3 Palembang. The method used in this research is a classroom action research method with planning, action, observation and reflection stages. Data collection techniques in this research are observation, documentation and tests. Furthermore, data analysis techniques in this research include qualitative data analysis techniques and quantitative data analysis techniques. This research consists of two cycles, each cycle going through planning, implementation, observation and reflection stages. The results of the research and discussion show that using a collaborative approach to material about scientific work using good steps can optimize student learning outcomes. This can be seen from the percentage of completeness of students' learning outcomes, namely starting from the experiment in cycle 1 it was 67.7% and increased in cycle II to 83.8%. The percentage of completeness of student learning outcomes obtained from cycle II has reached the success indicators set out in this research, namely achieving the Minimum Completeness Criteria (KKM) for Indonesian scientific work material with a score of â‰¥ 78 reaching more than 80%. So researchers can identify that using a collaborative approach can optimize student learning outcomes in getting to know scientific work in class XI SMA Negeri 3 Palembang.